FABRICATION AND ANALYSIS OF CALATROPIC GIGANTEAGFRP IN AIRCRAFT STRUCTURE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The composite materials are replacing the traditional materials, because of its superior propertiessuch as high tensile strength, low thermal expansion, high strength to weight ratio. The developments ofnew materials are on the anvil and are growing day by day. Fiber composites such as Calotropisgigantea– GFRP became more attractive due to their better properties which are using for Aircraftapplications. In this connection we are fabricating Calotropis gigantea– GFRPcomposite with twodifferent resins, vinyl resin and polypropylene resin. After fabricated Calotropis gigantea–Gyrocompasses send for mechanical tests like Tensile, flexural, and Impact for experimental study.